PENGARUH PROJECT BASED LEARNING BERBASIS VIDEO PROJECT TERHADAP HASIL BELAJAR TEKNIK LEMPAR LEMBING SISWA SEKOLAH DASAR: STUDI PRE-EXPERIMENTAL - Rizki, Dani; Maulidin (Journal Sport Science, Health and Tourism of Mandalika (Jontak) e-ISSN 2722-3116, 2026)
Project Based Learning (PjBL) is a student-centered learning model that emphasizes active student participation through project-based activities. In physical education learning, innovative teaching approaches are needed to improve students' motor skills and learning outcomes. However, the integration of Project Based Learning with video-based projects in elementary physical education remains limited. Therefore, this study aims to analyze the effect of Project Based Learning through video projects on students’ learning outcomes in javelin throwing techniques. This study employed a quantitative approach using a pre-experimental one group pretest–posttest design. The participants consisted of 25 fifth-grade students of SD Negeri 5 Mataram selected using purposive sampling. Data were collected through javelin throwing skill tests, observation sheets, and technical assessment rubrics. Data analysis included normality tests, homogeneity tests, and paired sample t-tests using SPSS with a significance level of 0.05. The results showed that the average pretest score was 51.36 and increased to 90.88 in the posttest. The paired sample t-test showed a significance value of p < 0.001, indicating a significant improvement in students’ learning outcomes. The findings suggest that the implementation of Project Based Learning through video projects effectively improves students’ understanding and technical skills in javelin throwing. Integrating project-based learning with digital media can enhance student engagement and learning outcomes in physical education.